Single cell census of human kidney organoids shows reproducibility and diminished off-target cells after transplantation - Ayshwarya Subramanian (Nature Portfolio, 2019)
How reproducible human kidney organoids derived from different iPSC lines are, and how faithful they are to human kidney tissue remain unclear. Here, the authors use four human iPSC lines to derive kidney organoids and show how organoid composition is reproducible, comparable to human tissue and of improved quality after transplantation.